2012
DOI: 10.1108/00483481211212940
|View full text |Cite
|
Sign up to set email alerts
|

An update of gender diversity in editorial boards: a longitudinal study of management journals

Abstract: PurposeThis study updates our knowledge of women's representation on the boards of scholarly management journals with a longitudinal analysis of the same over two decades. Design/methodology/approachThis study extends the work of Metz and Harzing (2009) Practical ImplicationsThis study's findings clearly indicate that there is still much that can be done to narrow the gender imbalance in most editorial boards of management journals. Monitoring women's representation in editorial boards of management journals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
40
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 30 publications
3
40
1
1
Order By: Relevance
“…Journal editors and editorial boards therefore play important roles as gatekeepers of knowledge within fields and the academic marketplace more broadly. Although we have seen reports of increased gender equality in academic journal editorial boards (e.g., Addis and Villa ; Metz and Harzing ; Metz, Harzing, and Zyphur ), these increases have not kept pace with the proportion of female scholars in various fields. In fact, “there is still substantial variability in women's level of representation on EBs [editorial boards] across journals in the same field of study” (Metz, Harzing, and Zyphur , 712).…”
mentioning
confidence: 92%
“…Journal editors and editorial boards therefore play important roles as gatekeepers of knowledge within fields and the academic marketplace more broadly. Although we have seen reports of increased gender equality in academic journal editorial boards (e.g., Addis and Villa ; Metz and Harzing ; Metz, Harzing, and Zyphur ), these increases have not kept pace with the proportion of female scholars in various fields. In fact, “there is still substantial variability in women's level of representation on EBs [editorial boards] across journals in the same field of study” (Metz, Harzing, and Zyphur , 712).…”
mentioning
confidence: 92%
“…The opportunity for homophilous interactions is determined by the demographics of the 572 gatekeeper pool, and the demographics of the gatekeepers differed significantly from those of 573 the authors, even for last authors, who tend to be more senior [59][60][61][62]. The underrepresentation 574 of women at eLife mirrors global trends-women comprise a minority of total authorships, yet 575 constitute an even smaller proportion of gatekeepers across many domains [14, [67][68][69][70][71][72][73][74]. Similarly, 576 gatekeepers at eLife were less geographically diverse than their authorship, reflecting the general 577 underrepresentation of the "global south" in leadership positions of international journals [75].…”
mentioning
confidence: 99%
“…However, Cho$et$al.,$p.$7" surveys in economics (Addis & Villa 2003;Green 1998), medicine (Galley & Colvin 2013;122" Keiser, Utzinger & Singer 2003), management (Metz & Harzing 2012), information systems 123" (Cabanac 2012), and anthropology (Stark et al 1997) have found comparable disparities in the 124" gender composition of editorial boards. Assuming the results for our focal journals are 125"…”
mentioning
confidence: 99%